Earthquake resistant design of structures - Duggal, S. K. (Oxford University Press, 2007)
Annotation Designed to serve as a textbook for students pursuing a B tech or BE program in civil engineering,Earthquake-resistant Design of Structuresexplains the different sources of damage that can be triggered by an earthquake and the conceptual method of earthquake-resistant design. The book will also be useful for postgraduate students of civil engineering, practicing engineers, and architects.The various topics in the book are presented in a systematic manner to ease understanding of concepts. After an introduction to earthquakes and ground motion, the easy-to-understand textbook provides detail chapters on structures and soli in terms of their seismic response. The need for placing importance on conceptual design is covered in detail by enumerating factors that cause damage and offering guidelines for efficient seismic-resistant design. The book emphasizes structural damage induced by vibration on timber, masonry, concrete, and steel buildings.
Keywords: Earthquake resistant design.; elektronické knihy; electronic books